Simplify the following:
((x^2 - 11 x + 30) (x^2 + 6 x + 5))/((x^2 - 25) (x - 5 x - 6))
The factors of 5 that sum to 6 are 5 and 1. So, x^2 + 6 x + 5 = (x + 5) (x + 1):
((x + 5) (x + 1) (x^2 - 11 x + 30))/((x^2 - 25) (x - 5 x - 6))
The factors of 30 that sum to -11 are -5 and -6. So, x^2 - 11 x + 30 = (x - 5) (x - 6):
((x - 5) (x - 6) (x + 5) (x + 1))/((x^2 - 25) (x - 5 x - 6))
x - 5 x = -4 x:
((x - 5) (x - 6) (x + 5) (x + 1))/((x^2 - 25) (-4 x - 6))
Factor -2 out of -4 x - 6:
((x - 5) (x - 6) (x + 5) (x + 1))/(-2 (2 x + 3) (x^2 - 25))
x^2 - 25 = x^2 - 5^2:
((x - 5) (x - 6) (x + 5) (x + 1))/(-2 (x^2 - 5^2) (2 x + 3))
Factor the difference of two squares. x^2 - 5^2 = (x - 5) (x + 5):
((x - 5) (x - 6) (x + 5) (x + 1))/(-2(x - 5) (x + 5) (2 x + 3))
((x - 5) (x - 6) (x + 5) (x + 1))/((x - 5) (x + 5) (-2) (2 x + 3)) = ((x - 5) (x + 5))/((x - 5) (x + 5))×((x - 6) (x + 1))/(-2 (2 x + 3)) = ((x - 6) (x + 1))/(-2 (2 x + 3)):
((x - 6) (x + 1))/(-2 (2 x + 3))
Multiply numerator and denominator of ((x - 6) (x + 1))/(-2 (2 x + 3)) by -1:
Answer: (-(x - 6) (x + 1))/(2 (2 x + 3))
Answer:
9 1/3, 12 1/2, 14 3/4
Step-by-step explanation:
I assume the formula you’re working with is A=b*h since nothing says otherwise...
((Patio 1))
So you have your area (147) and your base (15 3/4), now you need to plug them in, which should look like this:
147= 15 3/4*h
You need to isolate your h in order to get the missing number, so you should divide both sides by 15 3/4 OR 63/4 ((15*3—>60+3=63))
Dividing by a fraction is the equivalent of multiplying by its reciprocal... so
147 * 4/63 = 588/63 which can be simplified to 84/9 once both the numerator and denominator are divided by 7
In mixed number for it is 9 3/9 which simplified becomes 9 1/3
You solve the other similarly
This is the answer y= -x+3
Answer:
8
Step-by-step explanation:
3(8-m)=5m-40
you first distribute 3 through the parenthesis
24-3m=5m-40
Move the variable to the left and change sign
24-3m-5m=-40
now move the constant to the right
-3m-5m=-40-24
collect like terms
-8m=-40-24
-8m=-64
Divide both sides by -8 and negative divide negative number becomes positive
so m = 8
Equation- 2n+13=75
n is 31
Hope this helped.